Global, Regional, and National Burden of Iodine Deficiency in Reproductive Women From 1990 to 2019, and Projections to 2035: A Systematic Analysis for the Global Burden of Disease Study in 2019 - Lin J; Tan HL; Ge H (International Journal of Women's Health)
Jing Lin,1,2 Hai-Long Tan,2 Huan Ge3 1Department of General Surgery, Cancer Hospital of Xinjiang Medical University, Urumqi, Xinjiang, 830011, People’s Republic of China; 2Department of General Surgery, Xiangya Hospital Central South University, Changsha, Hunan, 410008, People’s Republic of China; 3Department of Respiratory Medicine, National Key Clinical Specialty, Branch of National Clinical Research Center for Respiratory Disease, Xiangya Hospital, Central South University, Changsha, Hunan, 410008, People’s Republic of ChinaCorrespondence: Huan Ge, Email gh414031694@163.comBackground: Iodine deficiency threatens women of reproductive-age (15– 49 years) worldwide, increasing risks of thyroid dysfunction and developmental abnormalities. Accurate trend prediction is essential for targeted prevention strategies.Purpose: To investigates the global, regional, and national disease burden of iodine deficiency among reproductive-age women from 1990 to 2019, as well as projected trends through 2035.Patients and methods: Using Global Burden of Disease 2019 data, we assessed prevalence, mortality, years lived with disability (YLDs), and disability-adjusted life years (DALYs) across 204 countries/territories (1990– 2019). Age-period-cohort Bayesian model was used to predict trends from 2020 to 2035.Results: In 2019, 81.4 million women of reproductive age globally had iodine deficiency (age-standardized prevalence: 2871.7/100,000), reflecting a 13.3% reduction since 1990. The condition caused 1.1 million YLDs (age-standardized rate: 38.4/100,000), marking a 27.4% decrease from 1990. Projections suggest sustained declines through 2035. Notably, a strong inverse correlation emerged between Socio-demographic Index (SDI) and disease burden, with a correlation coefficient of − 0.58 (95% CI: − 0.63 to − 0.53, p< 0.001). Geographically, the highest burden clustered in Central Sub-Saharan Africa, South Asia, and Eastern Sub-Saharan Africa, with Somalia, the Democratic Republic of the Congo, and Congo having the highest national prevalence.Conclusion: The global burden of iodine deficiency among women of reproductive age has decreased substantially since 1990. Nonetheless, considerable challenges persist in lower SDI regions, especially affecting women within the reproductive age. Addressing these inequities in global iodine nutrition and alleviate the iodine deficiency-related burden, targeted implementation strategies and continuous monitoring measures are urgently needed.Keywords: iodine deficiency, women of reproductive age, prevalence, years lived with disability